2017
DOI: 10.1002/jsfa.8268
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high voltage atmospheric cold plasma on white grape juice quality

Abstract: HVACP treatment of white grape juice at 80 kV for 2 min was found to be comparable to thermal pasteurization in all analyzed quality attributes. HVACP has shown the potential to be used as an alternative to thermal treatment of white grape juice. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
100
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(122 citation statements)
references
References 44 publications
(75 reference statements)
21
100
0
1
Order By: Relevance
“…This subsequently initiates a cascade of reactions which ultimately decrease the TPC. The results are in agreement with the existing studies on the effect of cold plasma on phenolics of white grape juice (Pankaj, Wan, Colonna, & Keener, ), orange juice (Almeida et al, ), and lettuce (Grzegorzewski, Ehlbeck, Schlüter, Kroh, & Rohn, ). Besides the reduction of TPC, the metabolites of phenolic degradation such as quercetin‐3‐rutinoside, quercetin‐3‐glucoside (Kovacevic et al, ), neochlorogenic acid, protocatechuic acid, and phloroglucinol carboxylic acid (Makris & Rossiter, ) are of significance due to their enhanced stability and radical scavenging activity (Heim, Tagliaferro, & Bobilya, ).…”
Section: Resultssupporting
confidence: 92%
“…This subsequently initiates a cascade of reactions which ultimately decrease the TPC. The results are in agreement with the existing studies on the effect of cold plasma on phenolics of white grape juice (Pankaj, Wan, Colonna, & Keener, ), orange juice (Almeida et al, ), and lettuce (Grzegorzewski, Ehlbeck, Schlüter, Kroh, & Rohn, ). Besides the reduction of TPC, the metabolites of phenolic degradation such as quercetin‐3‐rutinoside, quercetin‐3‐glucoside (Kovacevic et al, ), neochlorogenic acid, protocatechuic acid, and phloroglucinol carboxylic acid (Makris & Rossiter, ) are of significance due to their enhanced stability and radical scavenging activity (Heim, Tagliaferro, & Bobilya, ).…”
Section: Resultssupporting
confidence: 92%
“…The change of color quality might result from the polymerization of phenolic compounds induced by cold plasma (Bursac Kovacevic et al., ). Some studies have indicated that the cold plasma could change the color of fruit juices (Almeida et al., ; Bursac Kovacevic et al., ; Pankaj, Wan, Colonna, & Keener, ). Pankaj et al.…”
Section: Resultsmentioning
confidence: 99%
“…Pankaj et al. () applied a high voltage ACP (HVACP) to treat grape juice and also found that the color value a * and b * of grape juice changed. The change of color might be due to the oxidation reaction of pigment compounds and active species generated by ACP (Wang et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…It has been confirmed that plasma‐reactive oxygen species, such as Ar + and OH • , lead to etching of the upper epidermis of lettuce, which stimulates the release of flavonoids from the central vacuoles of the guard cells (Muhammad et al., ). An increase in the antioxidant activity could also be attributed to the incorporation of CP hydroxyl groups into the phenolic compounds (Pankaj, Wan, Colonna, & Keener, ).…”
Section: Resultsmentioning
confidence: 99%